Coordinating abilities in structure of special preparation of combat athletes - Klymenko A.I (Kharkov National Pedagogical University, 2010)
Development tendency of modern sport assumes high competition and as a result, training and competitive pressure. This requires from the coach to search for new methods of increasing effectiveness of the training process without increasing the pressure volume and intensiveness. One of the ways of solving this problem is the development of a method of increasing coordinating abilities. Several types of coordinating abilities of wrestlers. Deals with methodical peculiarities or perfection and means of increasing coordinating of sambo.